2015
DOI: 10.1667/rr14016.1
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 Alpha Regulates the Response of Primary Sarcomas to Radiation Therapy through a Cell Autonomous Mechanism

Abstract: Hypoxia is a major cause of radiation resistance, which may predispose to local recurrence after radiation therapy (RT). While hypoxia increases tumor cell survival after RT because there is less oxygen to oxidize damaged DNA, whether signaling pathways triggered by hypoxia contribute to radiation resistance is poorly understood. For example, intratumoral hypoxia can increase hypoxia inducible factor 1 alpha (HIF-1α), which may regulate pathways that contribute to radiation sensitization or radiation resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 46 publications
1
41
0
1
Order By: Relevance
“…In view of this decline in blood perfusion, it is not surprising that intratumour hypoxia is markedly increased under these conditions ( Figure 5). The aberrant increase in HIF-1a and its target genes, VEGF and CA9, in FSaII tumours observed in response to 15 Gy irradiation ( Figure 6) is in agreement with previous reports that high-dose irradiation induces significant upregulation of HIF-1a in various tumours [31,[35][36][37][38][39][40]43]. In the context of radiation-induced upregulation of HIF-1a, studies to date have shown that hypoxic cells in tumours are reoxygenated after irradiation and HIF-1a is activated in response to the reactive oxygens formed [36].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In view of this decline in blood perfusion, it is not surprising that intratumour hypoxia is markedly increased under these conditions ( Figure 5). The aberrant increase in HIF-1a and its target genes, VEGF and CA9, in FSaII tumours observed in response to 15 Gy irradiation ( Figure 6) is in agreement with previous reports that high-dose irradiation induces significant upregulation of HIF-1a in various tumours [31,[35][36][37][38][39][40]43]. In the context of radiation-induced upregulation of HIF-1a, studies to date have shown that hypoxic cells in tumours are reoxygenated after irradiation and HIF-1a is activated in response to the reactive oxygens formed [36].…”
Section: Discussionsupporting
confidence: 92%
“…This type of high-dose hypofractionated irradiation has been shown to induce vascular damage in tumours [28][29][30], in turn, triggering secondary or indirect tumour cell death [28,[31][32][33][34]. Importantly, recent studies have reported that high-dose irradiation can also induce activation of various cell survival signals such as HIF-1a and its target genes in tumour cells [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic role of HIF-1 is particularly interesting in relation to radiotherapy, which is frequently used in the adjuvant setting 37. HIF-1 has been suggested as a potential candidate for targeted inhibition to improve radiation outcome 38.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse primary sarcoma cell lines were generated from Pax7 CreER-T2 , p53 FL/FL , LSLNras G12D tumors as described previously 48 . Briefly, tumor tissue was excised and digested with 5 mg/mL Collagenase Type I at 37 °C for 45 mins.…”
Section: Generation Of Mouse Sarcoma Cell Lines and Crispr-based Pdh mentioning
confidence: 99%